Ortega for president: The religious rebirth of Sandinismo in Nicaragua. - Gooren, Henri (European Review of Latin American and Caribbean Studies, 2010)
This article analyses various connections between Daniel Ortega’s surprising victory in the presidential elections of 5 November 2006, his control of the Frente Sandinista de la Liberación Nacional (FSLN) party, and the changing religious context in Nicaragua, where Pentecostal churches now claim almost one quarter of the population. To achieve this, I draw from my fieldwork in Nicaragua in 2005 and 2006, which analysed competition for members between various religious groups in Managua: charismatic Catholics, the Assemblies of God, the neo-Pentecostal mega-church Hosanna, and the Mormon Church. How did Ortega manage to win the votes from so many religious people (evangelical Protestants and Roman Catholics alike)? And how does this case compare to similar cases of populist leaders in Latin America courting evangelicals, like Chávez in Venezuela and earlier Fujimori in Peru? Resumen: Ortega, presidente: el renacimiento religioso del sandinismo en NicaraguaEste artículo analiza varias conexiones entre la sorprendente victoria de Daniel Ortega en las elecciones presidenciales del 5 de noviembre de 2006, su control del partido Frente Sandinista de Liberación Nacional (FSLN) y el contexto religioso de Nicaragua, donde los pentecostales dicen representar a casi una cuarta parte de la población. Para el análisis me baso en mi trabajo de campo en Nicaragua en 2005 y 2006, en el que estudié a varios grupos religiosos que compiten en el reclutamiento de miembros en Managua: los católicos carismáticos, las Asambleas de Dios, la ‘mega-iglesia’ neopentecostal Hosanna y la iglesia mormona. ¿Cómo logró Ortega atraer los votos de tanta gente religiosa (evangélicos y católicos)? Y ¿cómo se compara este caso con otros similares en que líderes populistas conquistan el voto religioso, como Chávez en Venezuela y, antes, Fujimori en Perú?